Réponses

2014-01-15T23:34:40+01:00
Bonsoir,

G peut s'écrire de plusieurs manières.

G = 3(4x - 2)
    = 12x - 6
    = 2*6x - 6
    = 4*3x - 6
    = 3*2(2x - 1) = 6(2x - 1)

Si x = 5, alors G = 3(4x - 2) = 3(4*5 - 2)
                                               = 3(20 - 2)
                                               = 3*18
                                               = 54.

Si 4x - 2 = 7, alors G = 3(4x - 2) = 3*7
                                                   = 21

Si 12x = 11, alors G = 12x - 6 = 11 - 6
                                                   = 5


Si 6x = 5, alors G = 2*6x - 6 = 2*5 - 6
                                               = 10 - 6
                                               = 4

Si 2x - 1 = 3, alors G = 6(2x - 1) = 6*3
                                                       = 18

Si 3x = 25, alors G = 
4*3x - 6 = 4*25 - 6
                                                   = 100 - 6
                                                   = 94
 

merci et j’espère que c'est bon merci encore
  • bau
  • Ambitieux
2014-01-16T01:37:36+01:00
x = 5  G = 3 x 18 G = 54
4 x – 2 = 7  G = 3 x 7 G = 21
12 x = 11  G = 11 – 6 G = 5
6 x = 5  G = 10 – 6 G = 4
2 x – 1 = 3  G = 6 x 3 G = 18
3 x = 25 G = 100 – 6 G = 94